Exploration : what are missing in young offenders? Education and executive function? - Choo, Melissa Hui Lin (2009)
This study examined education and executive function in male young offenders and undergraduates in Singapore. The Stroop and arithmetic switching tasks were used to investigate the developmental status of executive function. No significant interference difference was found between inmates and undergraduates. However, young offenders made significantly more errors than the undergraduates on the incongruent trials in the Stroop task. There was a significant difference in switch cost between the young offenders and undergraduates; inmates took longer time to switch between operations than undergraduates. Education was found to be correlated with inhibitory control, component time and switch cost. The findings indicated that young offenders were less cognitively flexible; and education might be an explanation to the difference in executive function between young offenders and undergraduate.